Age-Related Differential Stimulation of Immune Response by Babesia microti and Borrelia burgdorferi During Acute Phase of Infection Affects Disease Severity - Djokic, Vitomir; Primus, Shekerah; Akoolo, Lavoisier; Chakraborti, Monideep; Parveen, Nikhat (Frontiers in Immunology, 2018)
Lyme disease is the most prominent tick-borne disease with 300,000 cases estimated by CDC every year while ~2000 cases of babesiosis occur per year in the United States. Simultaneous infection with Babesia microti and Borrelia burgdorferi are now the most common tick-transmitted coinfections in the U.S.A., and they are a serious health problem because coinfected patients show more intense and persisting disease symptoms. B. burgdorferi is an extracellular spirochete responsible for systemic Lyme disease while B. microti is a protozoan that infects erythrocytes and causes babesiosis. Immune status and spleen health are important for resolution of babesiosis, which is more severe and even fatal in the elderly and splenectomized patients. Therefore, we investigated the effect of each pathogen on host immune response and consequently on severity of disease manifestations in both young, and 30 weeks old C3H mice. At the acute stage of infection, Th1 polarization in young mice spleen was associated with increased IFN-γ and TNF-α producing T cells and a high Tregs/Th17 ratio. Together, these changes could help in the resolution of both infections in young mice and also prevent fatality by B. microti infection as observed with WA-1 strain of Babesia. In older mature mice, Th2 polarization at acute phase of B. burgdorferi infection could play a more effective role in preventing Lyme disease symptoms. As a result, enhanced B. burgdorferi survival and increased tissue colonization results in severe Lyme arthritis only in young coinfected mice. At three weeks post-infection, diminished pathogen-specific antibody production in coinfected young, but not older mice, as compared to mice infected with each pathogen individually may also contribute to increased inflammation observed due to B. burgdorferi infection, thus causing persistent Lyme disease observed in coinfected mice and reported in patients. Thus, higher combined proinflammatory response to B. burgdorferi due to Th1 and Th17 cells likely reduced B. microti parasitemia significantly only in young mice later in infection, while the presence of B. microti reduced humoral immunity later in infection and enhanced tissue colonization by Lyme spirochetes in these mice even at the acute stage, thereby increasing inflammatory arthritis.